Career goals of a private hospital nurses and career opportunities offered to them - ERGÜN, YASEMİN (ELSEVIER SCIENCE BV, 2012)
Nurses' career goals align with career aims of the organization is extremely important. And also it is very important to prepare for career changes to achieve their career goals. Career progress of nurses and increasing the satisfactions levels of their profession provide retention skilled personnel and a high in service quality of the organization. The aim of the study was to determine career goals of nurses and career opportunities offered to them. This descriptive study was carried out between December 2008 and January 2009. Population of the study consisted of a total of 187 voluntary nurses working in a private hospital in Istanbul. Data was collected using questionnaire form. Descriptive statistical methods, parametric and non-parametric tests were used for evaluation of data. Statistically significant differences found between the defines such as having career goals and age, education, being single and being childless of nurses. It was found that the nurses had career goals; they needed training in terms of career planning; the organization they worked offered managerial arrangements for career development, however these managerial and organizational supports were not adequately shared with the employees. Many proposals which will guide career planning are improved by these outcome.
Keywords: Nurse; Career; Career Goals; Career Opportunities; ORGANIZATIONAL COMMITMENT; JOB